2016
DOI: 10.1021/acs.nanolett.5b05095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High Density of Stacking Faults on the Young’s Modulus of GaAs Nanowires

Abstract: Stacking faults (SFs) are commonly observed crystalline defects in III-V semiconductor nanowires (NWs) that affect a variety of physical properties. Understanding the effect of SFs on NW mechanical properties is critical to NW applications in nanodevices. In this study, the Young's moduli of GaAs NWs with two distinct structures, defect-free single crystalline wurtzite (WZ) and highly defective wurtzite containing a high density of SFs (WZ-SF), are investigated using combined in situ compression transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 63 publications
4
64
1
Order By: Relevance
“…In situ TEM tests provide an ideal tool for studying the actual deformation mechanisms involving the dislocation activities of NWs under tension/compression. In fact, in situ TEM techniques have now become the most widely used method for characterizing a range of NWs, such as Si,101, 102 GaAs103, 104, 105, 106 ZnO,107, 108 VO 2 109. GaN,99, 110, 111 ZnTe,112 Ag,113, 114, 115, 116, 117 Ni118, 119 Cu,120, 121, 122 and metallic glasses 123, 124…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…In situ TEM tests provide an ideal tool for studying the actual deformation mechanisms involving the dislocation activities of NWs under tension/compression. In fact, in situ TEM techniques have now become the most widely used method for characterizing a range of NWs, such as Si,101, 102 GaAs103, 104, 105, 106 ZnO,107, 108 VO 2 109. GaN,99, 110, 111 ZnTe,112 Ag,113, 114, 115, 116, 117 Ni118, 119 Cu,120, 121, 122 and metallic glasses 123, 124…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…Recently, the Liao and co‐workers reported that GaAs NWs exhibited a larger Young's modulus when they have stacking faults than for the ZB or WZ phase . The stiffening effect of the stacking faults has been attributed to the changes in the interatomic bonding configuration at the stacking faults.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of phase mixing in NWs has not yet been fully understood. Nevertheless, exploring how the mechanical properties of NWs are affected by the stacking faults is of great importance for various promising applications . It has been reported that GaAs NWs exhibit higher Young's moduli when they have stacking faults .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13] It has been found that the fundamental dislocation mechanisms that initiate and sustain plastic flow and fracture in nano-sized materials are considerably different from their bulk counterparts. [14][15][16][17][18][19] For small sized metals with the face-centered-cubic (FCC) structure, it is well established that their plastic deformation is governed by dislocations escaping more quickly than they can multiply, leaving the sample free of dislocations (termed as "dislocation starvation").…”
Section: Introductionmentioning
confidence: 99%